2011
DOI: 10.1007/s11010-011-1188-4
|View full text |Cite
|
Sign up to set email alerts
|

MAOA, MTHFR, and TNF-β genes polymorphisms and personality traits in the pathogenesis of migraine

Abstract: Migraine is a multifactorial disease with various factors, such as genetic polymorphisms and personality traits, but the contribution of those factors is not clear. To clarify the pathogenesis of migraine, the contributions of genetic polymorphisms and personality traits were simultaneously investigated using multivariate analysis. Ninety-one migraine patients and 119 non-headache healthy volunteers were enrolled. The 12 gene polymorphisms analysis and NEO-FFI personality test were performed. At first, the uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 64 publications
1
21
1
Order By: Relevance
“…In a study by Filic V et al, no association was detected in migraine patients with and without aura [22]. Another study revealed that plasma 5-HT levels in migraine patients without aura are lower when compared to controls, based on the higher G allele and G/G genotype of T941G polymorphisms of MAOA in migraine patients [25]. Our results failed to show a relationship between MAO enzymes gene polymorphisms and TTH.…”
Section: Discussioncontrasting
confidence: 76%
“…In a study by Filic V et al, no association was detected in migraine patients with and without aura [22]. Another study revealed that plasma 5-HT levels in migraine patients without aura are lower when compared to controls, based on the higher G allele and G/G genotype of T941G polymorphisms of MAOA in migraine patients [25]. Our results failed to show a relationship between MAO enzymes gene polymorphisms and TTH.…”
Section: Discussioncontrasting
confidence: 76%
“…Migraine [5,28] and depression [29,30] are known to be associated with high neuroticism. Kanki et al [31] reported that the comorbidity with depression is observed in 12.9% of the patients with migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Migraines are usually characterized by severe pain on one or both sides of the head and at times disturbed vision [3,4,5]. Migraine is a multifactorial disease, and gene polymorphisms and personality traits both contribute to its pathogenesis [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, several follow-up studies have been continuously carried out in an effort to replicate the initial finding. Some were successful [16], [17], whereas others failed [18], [19]. Multiple factors including selection of diverse populations, different control sources, and misclassification of genotypes may individually or jointly result in the controversy, but the main source can attribute to the various numbers of subjects used in each study.…”
Section: Introductionmentioning
confidence: 99%